2002
DOI: 10.1002/ppul.10212
|View full text |Cite
|
Sign up to set email alerts
|

Use of urokinase in childhood pleural empyema

Abstract: Urokinase is an enzyme with a fibrinolytic effect that facilitates pleural empyema drainage through a chest tube. The aim of this study was to assess the risk of pneumothorax, the need for pleural debridement surgery, the persistence of fever, and the number of days in hospital in a group of children with parapneumonic pleural empyema treated with urokinase. This was an uncontrolled retrospective study on children suffering from parapneumonic empyema. Data collected on 17 children treated with urokinase were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 29 publications
0
34
0
2
Order By: Relevance
“…In cases where drainage is slow, due to the fluid being thick or loculated, twice-daily intrapleural fibrinolytics such as urokinase have been shown to reduce duration of hospital stay [52], incidence of residual pleural thickening [56] and allow resolution of empyema without surgical intervention in up to 93% of cases [52]. Although in one small study, the failure rate was reported at almost 70% [57], in our experience, in 180 children with empyema who required chest drains between 2002 and 2007, of whom 80% received intrapleural urokinase, ,3% went on to have a surgical procedure. Chest tubes are removed when f50 mL per day is draining and the integrity of the drain is confirmed; chest radiographs should be repeated 3-4 h after drain removal to ensure that re-accumulation or pneumothorax has not occurred.…”
Section: Parapneumonic Effusion/empyemamentioning
confidence: 99%
“…In cases where drainage is slow, due to the fluid being thick or loculated, twice-daily intrapleural fibrinolytics such as urokinase have been shown to reduce duration of hospital stay [52], incidence of residual pleural thickening [56] and allow resolution of empyema without surgical intervention in up to 93% of cases [52]. Although in one small study, the failure rate was reported at almost 70% [57], in our experience, in 180 children with empyema who required chest drains between 2002 and 2007, of whom 80% received intrapleural urokinase, ,3% went on to have a surgical procedure. Chest tubes are removed when f50 mL per day is draining and the integrity of the drain is confirmed; chest radiographs should be repeated 3-4 h after drain removal to ensure that re-accumulation or pneumothorax has not occurred.…”
Section: Parapneumonic Effusion/empyemamentioning
confidence: 99%
“…81 UK and streptokinase have the same effectiveness in treating PPE and empyemas. 62 Urokinase is preferred over streptokinase because of its lower allergenic risk, but it is more expensive.…”
Section: So Which Fibrinolytic To Use?mentioning
confidence: 99%
“…fibrinolytic therapy; fibrinolysis; plasminogen activator inhibitor 1; pleural injury; urokinase; tissue plasminogen activator INTRAPLEURAL FIBRINOLYTIC THERAPY (IPFT) activates the endogenous fibrinolytic system, resolving intrapleural adhesions and complex fibrinous deposits that sequester pockets of inflammation loculations, thus improving drainage and clinical outcome, in part by decreasing surgical interventions (10). There are multiple reports of successful (88 -100% efficacy) IPFT in adult (1,7,8,16,17,29,42,47,48,66,67,72) and in pediatric (2,3,6,11,20,40,41,58,59,61,63,67) patients with empyema although outcomes in adult patients are inconsistent in these trials. Thus IPFT represents a less invasive and costly alternative to video-assisted thoracic surgery or other surgical interventions, which demonstrate comparable efficacy (16,44,45,58,60,71) in pediatric practice.…”
mentioning
confidence: 99%